Pediatric classical Hodgkin lymphoma. (5th April 2021) - Lo, Andrea C.; Dieckmann, Karin; Pelz, Tanja; Gallop‐Evans, Eve; Engenhart‐Cabillic, Rita; Vordermark, Dirk; Kelly, Kara M.; Schwartz, Cindy L.; Constine, Louis S.; Roberts, Kenneth; Hodgson, David
Abstract: Over the past century, classical Hodgkin lymphoma (HL) has been transformed from a uniformly fatal disease to one of the most curable cancers. Given the high cure rate, a major focus of classical HL management is reducing the use of radiation therapy (RT) and chemotherapy agents such as procarbazine and doxorubicin to minimize long‐term toxicities. In both North America and Europe, an important philosophy in the management of classical HL is to guide the intensity of treatment according to the risk category of the disease. The main factors used for risk classification are tumor stage, bulk of disease, and the presence of B symptoms. Response to chemotherapy is an important factor guiding the utilization of RT in ongoing Children's Oncology Group (COG) and European Network Pediatric Hodgkin Lymphoma (EuroNet‐PHL) trials. Both trial groups have transitioned to reduced RT volumes that target the highest risk sites using highly conformal techniques, along with standard or intensified chemotherapy regimens to improve outcomes in higher risk patients. However, given the potential acute toxicities of intensified chemotherapy, immunoregulatory drugs are being investigated in upcoming trials. The purpose of this review is to summarize current approaches to treating pediatric classical HL according to the COG and EuroNet‐PHL.